Does the audiogram shape influence the intracochlear recording of Electrocochleography during and after cochlear implantation? - Haumann, Sabine; Timm, Max E.; Büchner, Andreas; Lenarz, Thomas; Salcher, Rolf B. (Frontiers in Neuroscience, 2025)
During cochlear implant (CI) surgery, it is desirable to perform intraoperative measurements such as Electrocochleography (ECochG) to monitor the inner ear function and thereby to support the preservation of residual hearing. However, a significant challenge arises as the recording location of intracochlear ECochG via the CI electrode changes during electrode insertion. This study aimed to investigate the relationships between intracochlear ECochG recordings, the position of the recording contact within the cochlea relative to its anatomy, and the implications for frequency and residual hearing preservation. Intraoperative ECochG recordings were conducted using the CI electrode (MED-EL) during the insertion of hearing preservation electrodes and after the insertion process. Recordings were continuously conducted using the most apical electrode (contact 1) during insertion. After insertion, the recordings were performed on all different electrode contacts. The electrode location in the cochlea during insertion was estimated using mathematical models and preoperative clinical imaging, while the postoperative electrode position was determined using postoperative clinical imaging. The study involved 10 adult CI recipients. In those with good low-frequency hearing, an increase in signal amplitude was observed, with the highest amplitudes closest to the stimulation frequency generators, and no phase change was observed. Conversely, patients with flat hearing loss exhibited a second peak with an opposite phase in the medial area of the cochlea. This study is the first to suggest that the pattern of the preoperative audiogram may influence the ECochG outcomes measured intraoperatively. Specifically, the ECochG responses during insertion appeared to behave as expected with good low-frequency hearing, while with flat hearing loss there appear to be further effects. These findings indicate that this approach can provide valuable information for the interpretation of intracochlearly recorded ECochG signals.